Reviewing Wind Speed and Energy Distribution in Malaysia - S. M., Lawan; W. A. W. Z., Abidin; W. Y., Chai; A., Baharun; T., Masri (European Academic Research, 2014)
Recent increase on negative issues related to global warming, greenhouse gases and other environmental concerns, the awareness in promoting alternative energy sources have increased significantly. Renewable energy is the most promising and sustainable energy source that will sustain and maintain environment; in particular,wind energy is considered as the clean and perfect solution to present environmental worries as well as to counter the limited hydrocarbon reserves that last for (30-40) years. This paper is to review recent wind speed and energy distribution in Malaysia and enumerate the potentials of using the available resources for wind power generation in the country. The extractable power output in a wind turbine is directly proportional to the speed cubed. Due to the location of the country in the equatorial zone, the annual mean wind speed falls within class 1, which ranges from 2.0-5.0m/s based on recent studies conducted by many researchers.